Pengaruh Profitabilitas, Leverage Dan Ukuran Perusahaan Terhadap Harga Saham Pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di BEI - Rizki Harnita; Nur Ahmadi Bi Rahmani; Khairina Tambunan (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The purpose of this study is to determine the effect of profitability, leverage and company size on stock prices in property and real estate companies listed on the Indonesia Stock Exchange (IDX). In this study using quantitative methods with an associative approach. The population used in this study is the financial statements of property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period, which is 21 companies. In this study, samples were taken using purposive sampling techniques based on certain criteria. The secondary data obtained were analyzed through the Eviews 12 Software program. The results of the first study show that Profitability does not have a significant effect on Stock Price. Secondly, it shows that Leverage has a significant effect on Share Price. Third, it shows that Company Size has a significant effect on Stock Price. Fourth, simultaneously Profitability, Leverage and Company Size have a significant effect on Share Price.